2010
DOI: 10.5009/gnl.2010.4.2.201
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CYP2C19 Polymorphism on Eradication of Helicobacter pylori: A Prospective Randomized Study of Lansoprazole and Rabeprazole

Abstract: Background/Aims: The CYP2C19 polymorphism plays an important role in the metabolism of various proton-pump inhibitors. Several trials have produced conflicting data on eradication rates of Helicobacter pylori (H. pylori) among CYP2C19 genotypes. We investigated whether the CYP2C19 genotype affects the eradication rate of H. pylori by direct comparing the effects of lansoprazole-and rabeprazole-based triple therapies. Methods: A total of 492 patients infected with H. pylori was randomly treated with either 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…CYP2C19 genotypes may influence the metabolism of various PPIs, and the use of high‐dose or low‐dose PPI may be related to the efficacy of bismuth‐containing therapies . We chose rabeprazole 20 mg twice daily, because rabeprazole is not affected by CYP2C19 genetics . We also analyzed the effect of CYP2C19 polymorphism, and found that 23 patients had the Hom‐EM CYP2C19 genotype, but without obvious statistical significance (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2C19 genotypes may influence the metabolism of various PPIs, and the use of high‐dose or low‐dose PPI may be related to the efficacy of bismuth‐containing therapies . We chose rabeprazole 20 mg twice daily, because rabeprazole is not affected by CYP2C19 genetics . We also analyzed the effect of CYP2C19 polymorphism, and found that 23 patients had the Hom‐EM CYP2C19 genotype, but without obvious statistical significance (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…We also analyzed the effect of CYP2C19 polymorphism, and found that 23 patients had the Hom‐EM CYP2C19 genotype, but without obvious statistical significance (Table ). The choice of PPI may diminish the impact of CYP2C19 genotypes . Interaction between PPIs and clopidogrel has recently been a hot issue.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the non-enzymatic pathway, a small amount of rabeprazole is converted into desmethyl rabeprazole and rabeprazole sulfone by CYP2C19 and CYP3A4, respectively [43,49,62]. Consequently, a number of studies have reported similar values for drug exposure, efficacy and clearance in both healthy volunteers and patients regardless of CYP2C19 genotype status [47,51,55,64,65]. …”
Section: Proton Pump Inhibitorsmentioning
confidence: 99%
“…To our knowledge [55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71], the effect of CYP2C19 polymorphisms on H. pylori eradication rate has not been evaluated in children. In randomized, double-blind, placebo-controlled studies of PPI-based triple eradication therapies for H. pylori in children the range of eradication rates has varied between 68 and 74% according to intention-to-treat analysis, and between 69 and 80% per protocol [4].…”
Section: Developmental and Genetic Pharmacology Of Ppismentioning
confidence: 99%
“…Because of the ease of testing, this test may become incorporated in routine practice [54]. However, studies in adults have presented evidence for or against the influence of PPI-related CYP2C19 polymorphisms on eradication rates [55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71]. The systematic review by Klotz et al [72] suggested that HetEM and PM are associated with a significantly higher H. pylori eradication rate in omeprazole and lansoprazole users combined versus HomEMs.…”
Section: Developmental and Genetic Pharmacology Of Ppismentioning
confidence: 99%